History in mathematics education : an ICMI study - Fauvel, John; Maanen, J. A. van (Jan A.) (New ICMI Study Series, 2000)
This text investigates how the learning and teaching of mathematics can be improved through integrating the history of mathematics into all aspects of mathematics education: lessons, homework, texts, lectures, projects, assessment, and curricula. Most of the leading specialists in the field have contributed to this book, whose topics include the integration of history in the classroom, its value in the training of teachers, and historical support for particular subjects and for students with diverse educational requirements. Resulting from an international study on behalf of ICMI (the International Commission of Mathematics Instruction), the text draws upon evidence from the experience of teachers as well as national curricula, textbooks, teacher education practices, and research perspectives across the world.